1995
DOI: 10.1016/0885-3924(95)00086-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of a topical refrigerant anesthetic to reduce injection pain in children

Abstract: Early childhood experiences with painful injections may lead to anxiety and fear. These reactions need not develop if steps are taken to reduce the pain associated with injections. The purpose of this study was to assess the efficacy of a refrigerant topical anesthetic in reducing injection pain in preschool children experiencing routine diphtheria-pertussis-tetanus (DPT) immunizations. This double-blind placebo-controlled study was conducted in community health clinics in conjunction with ongoing immunization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 23 publications
0
50
0
3
Order By: Relevance
“…This is especially noteworthy since evidence from the small number of pediatric clinical trials studies suggests that PR might be even more pronounced in children compared to adults (6)(7)(8). Clinical trials of local anesthetics (9,10) as well as a venipuncture study (11) emphasize the significance of PR in children. From a neurobiological perspective this is even more interesting since the prefrontal cortex (PFC) has repeatedly been implicated in the mediation of cognitive top-down expectation-related PR (12)(13)(14)(15) and given that this neural network undergoes considerable maturation during childhood (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially noteworthy since evidence from the small number of pediatric clinical trials studies suggests that PR might be even more pronounced in children compared to adults (6)(7)(8). Clinical trials of local anesthetics (9,10) as well as a venipuncture study (11) emphasize the significance of PR in children. From a neurobiological perspective this is even more interesting since the prefrontal cortex (PFC) has repeatedly been implicated in the mediation of cognitive top-down expectation-related PR (12)(13)(14)(15) and given that this neural network undergoes considerable maturation during childhood (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…15 Two studies compared the effectiveness of vapocoolant spray with a placebo in reducing vaccination pain. 15,17 Cohen et al 17 17 The analysis of the CAMPIS and VAS scoring did not find significant support for vapocoolant in reducing vaccination pain. However, the sample size (n=57) was insufficient to accurately identify any differences between the treatment and placebo groups.…”
Section: Topical Anestheticsmentioning
confidence: 99%
“…[15][16][17][18][19] Vapocoolant and lidocaine-prilocaine cream (5% eutectic emulsion of lidocaine [25 mg/g] and prilocaine [25 mg/g]) are both topical anesthetics approved for pain reduction during pediatric procedures, such as vaccinations. The studies investigated the effectiveness of these topical anesthetics.…”
Section: Topical Anestheticsmentioning
confidence: 99%
“…Other studies have shown that the use of cryoanalgesic sprays can be helpful in assuring adherence to proper vaccination scheduling in the pediatric population (2,3). Studies document that the use of refrigerant spray can significantly reduce injection pain, making the office experience less objectionable and compliance more likely (2)(3)(4). Vapocoolant sprays have also been used to manage myofascial trigger points and to lessen the pain of analgesic injection for dental procedures (5).…”
mentioning
confidence: 99%